Competence Multicultural Teachers Amidst Demographic Shifts: Implications for Educational Services - Iskandar, Rangga Bhakty; Hariyati, Nunuk; Mariana, Neni; Amalia, Kaniati; Khamidi, Amrozi (Universitas Pahlawan Tuanku Tambusai, 2025)
Global demographic shifts have made classrooms increasingly multicultural, demanding adequate multicultural competence from educators. This article aims to examine the urgency of teachers' multicultural competence in addressing the challenges of diversity and its implications for the quality of educational services. Using an integrative literature review method, this article analyzes 38 empirical studies and theoretical sources published between 2020 and 2025, sourced from databases such as Scopus, ERIC, ScienceDirect, and Google Scholar. Thematic analysis was employed to identify key patterns and themes related to multicultural competence and educational service quality. The findings indicate that multicultural competence plays an important role in supporting various dimensions of educational service quality. The article also emphasizes the need to strengthen teachers' capacities in responding to multiculturalism to create inclusive, responsive, and high-quality educational services. These findings offer strategic implications for education policy development, teacher training, and the evaluation of diversity-based educational service quality.